Endogenous IAA affected fluoranthene accumulation by regulating H+-ATPase and SOD activity in ryegrass - Xu, Yuanzhou; Li, Yunyun; Xiao, Zhuoliang; Zhang, Xinyue; Jiao, Jiaguo; Zhang, Huijuan; Li, Huixin; Hu, Feng; Xu, Li (Ecotoxicology and environmental safety, 2024)
This study explores the role of endogenous indole-3-acetic acid (IAA) in modulating plant responses to pollution stress and its effect on pollutant accumulation, with a focus on fluoranthene (Flu) in ryegrass. To elucidate the mechanism, we employed an IAA promoter (α-aminobutyric acid [α-AB]) and an IAA inhibitor (naphthylphthalamic acid [NPA]) to regulate IAA levels and analyze Flu uptake characteristics. The experimental setup included a Flu treatment group (ryegrass with Flu addition) and a control group (ryegrass without Flu). Our findings demonstrate that Flu treatment enhanced IAA content and plant growth in ryegrass compared to the control. The Flu+AB treatment further enhanced these effects, while the Flu+NPA treatment exhibited a contrasting trend. Moreover, Flu+AB treatment led to increased Flu accumulation, in contrast to the inhibitory effect observed with Flu+NPA treatment. Flu treatment also enhanced the activities of key antioxidant enzymes (SOD, POD, CAT) and increased soluble sugar and protein levels, indicative of enzymatic and nonenzymatic defense responses, respectively. The Flu+AB treatment amplified these responses, whereas the Flu+NPA treatment attenuated them. Significantly, Flu treatment raised H+-ATPase activity compared to the control, an effect further elevated by Flu+AB treatment and diminished by Flu+NPA treatment. A random forest analysis suggested that Flu accumulation dependency varied under different treatments: it relied more on H+-ATPase activity under Flu+AB treatment and more on SOD activity under Flu+NPA treatment. Additionally, Flu+AB treatment boosted the transpiration rate in ryegrass, thereby increasing the Flu translocation factor, a trend reversed by Flu+NPA treatment. This research highlights crucial factors influencing Flu accumulation in ryegrass, offering potential new avenues for controlling the gathering of contaminants within plant systems. •IAA regulated ryegrass growth and antioxidant reactions to affect Flu uptake.•Transpiration rate affected Flu transport.•Soluble sugar and soluble protein content involved in Flu accumulation.•H+-ATPase activity was the key factor for Flu uptake under Flu+AB treatment.•SOD activity was important for Flu uptake under Flu+NPA treatment.